The kinmeteki analysis of variable pay in the development of its relationship with the completion of the shooting and javelin throwers for the national team for youth - Thamer, Ahmed (Journal of Physical Education, 2017)
The research aims to recognize the value of payment variable in the development of chucking the effectiveness of the javelin to the archers the national youth team and diagnose areas of strength and weaknesses, as well as to identify the relationship and the proportion of influential contribution between payment variable in the development of chucking of the effectiveness of the spear and achievement of archers National Youth team throw, as the researcher used descriptive approach to get to achieve the objectives of the study after it was determined the means of data and devices used to collect and how to be configured to hold the main trial as well as creating special devices to extract variable Find a device metric foot Scanner Foot scan, and then was Amaaljt variable statistically across the bag statistical Social Sciences spss been discussion Results on the basis of circles arithmetic values and standard deviations and the law of contribution ratio. Through the conclusion reached by the researcher has developed the following recommendations: 1. Emphasize the importance of using modern equipment in the analysis and imaging to see changes in the kinetic tracks mechanical errors accurately technical performance, especially for the development of chucking in the effectiveness of the javelin. 2. corrective action program to address all technical errors contained in the technical performance of Rami and get rid of the weaknesses associated with the Status Bmdiat throwing motion. Confirmation to allocate more time to train the technique to increase achievement, especially in activities that rely on technical performance. The trainers of the effectiveness of the javelin to the category of young people to know the contribution of physical and motor abilities of their players ratios.